Perancangan Sistem Antrian Protokol Kesehatan Memasuki Kampus untuk Mengoptimalkan Waktu Tunggu, Jumlah Antrian, dan Biaya Investasi Alat - Kristian Ismartaya (Jurnal Rekayasa Sistem Industri, 2023)
Politeknik ATMI Surakarta applies a health protocol to get into campus area, which consists of body temperature check and disinfectant spray. Existing health protocol supported by 1 automatic temperature checker and 4 automatic disinfectant spray booths. There is no evaluation has been carried out yet regarding to effectiveness and efficiency of facilities utility. There are queue problems, especially at critical time at morning shift from 07.00 WIB to 07.30 WIB and the system output has not been able to reach about 650 entities within 30 minutes. This system is a terminating simulation with 30 minutes of replication length. Simulation design is carried out to find the best system solution that achieves the entities number of output target, with evaluation based on queue waiting time, number of queues, cost factors, and percentage of facility utilities. The simulation system is made with ARENA software. Design solutions are compared and ranked. Selection of solutions based on the best design rating. The results showed that at the critical time 07.00 WIB - 07.30 WIB it was necessary to have 2 automatic temperature checking devices and 3 disinfectant chambers (Multi Channel - Multi Phase). This design produces an output of about 687 entities, a waiting time of 0.75 minutes, 8.46 entities of queue, and cost of Rp. 88,411.64. At regular times, 1 automatic temperature checker and 1 disinfectant chamber (Multi Channel - Single Phase) are needed. This design produces system output of about 262 entities, waiting time of 0.22 minutes, 2.01 entities of queues, and cost of Rp. 36,399.43.